Linguistic and Economic Adjustment among Immigrants in Israel - Barry R. Chiswick; Uzi Rebhun; Nadia Beider (Institute for the Study of Labor (IZA), 2016)
This paper analyzes the Hebrew language proficiency, probability of employment, and labor market earnings of immigrants in Israel. It uses the 2010/11 Immigrant Absorption Survey conducted by the Israeli Central Bureau of Statistics. Unique features of the analysis include the study of long-duration immigrants (3 to 20 years), and analyses for: males and females, primary reasons for immigration, the subsidized intensive Hebrew language training program (ulpan), Ethiopian Jews, and Jewish and non-Jewish immigrants from the Former Soviet Union (FSU), in addition to standard immigration, demographic, and human capital variables. Results from multivariate analyses largely accord with the "standard theoretical model" of language proficiency regarding the mechanisms of "exposure", "efficiency", and "economic incentives". Acquaintance with the local language, on its part, increases the likelihood of being employed, and it has positive earnings outcomes. We discuss implications of the findings for public policy which can improve the adjustment of these new immigrants into their new society hence also moderate inter-group tensions.
Keywords: F22; J15; J24; J61; 330; immigrants; Israel; language proficiency; employment; earnings; motive for immigration; ulpan